Epidemiology and location of primary retrieval missions in a Scottish aeromedical service. (April 2019) - Neagle, Gregg; Curatolo, Lisa; Ferris, John; Donald, Mike; Hearns, Stephen; Corfield, Alasdair R.
Abstract : Introduction: Prehospital critical care teams comprising an appropriately trained physician and paramedic or nurse have been associated with improved outcomes in selected trauma patients. These teams are a scarce and expensive resource, especially when delivered by rotary air assets. The optimal tasking of prehospital critical care teams is therefore vital and remains a subject of debate. Emergency Medical Retrieval Service (EMRS) provides a prehospital critical care response team to incidents over a large area of Scotland either by air or by road. Methods: A convenience sample of consecutive EMRS missions covering a period of 18 months from May 2013 to January 2015 was taken. These missions were matched with the ambulance service information on geographical location of the incident. In order to assess the appropriateness of tasking, interventions undertaken on each mission were analysed and divided into two subcategories: 'critical care interventions' and 'advanced medical interventions'. A tasking was deemed appropriate if it included either category of intervention or if a patient was pronounced life extinct at the scene. Results: A total of 1279 primary missions were undertaken during the study period. Of these, 493 primary missions met the inclusion criteria and generated complete location data. The median distance to scene was calculated as 5.6 miles for land responses and 34.2 miles for air responses. Overall, critical care interventions were performed on 17% (84/493) of patients. A further 21% (102/493) of patients had an advanced medical intervention. Including those patients for whom life was pronounced extinct on scene by the EMRS team, a total of 42% (206/493) taskings were appropriate. Discussion: Overall, our data show a wide geographical spread of tasking for our service, which is in keeping with other suburban/rural models of prehospital care. Tasking accuracy is also comparable to the accuracy shown by other similar services.